Métodos de valoración de los inventarios para la gestión financiera. - Cobos Leon, Guisela Dora (2017)
The basis for any type of organization is the purchase and sale of goods, from this point on, it is demonstrated the importance of the correct management of inventories. Proper inventory management allows the organization to maintain control because it contributes to cost reduction. Thus, in this context, the application of adequate inventory management becomes the best option in reducing costs and improving the economic efficiency of organizations, among the reasons is the increase in service levels to the customer, the increase of liquidity, and the preparation of the companies before the continuous movement of the demand. The general objective of the present titling work is to: Establish a system of inventory management, which allows the administration an optimum performance according to the activities that are developed, increasing the efficiency and effectiveness in the activities carried out in the company M.J. Towers. In order to achieve the goals set, the methodology of the present research work was based on a qualitative and quantitative approach, thus determining the importance of inventory management and the implementation of valuation methods for the company MJ Torres de the city of Machala. A documentary and field research was also carried out. Among the instruments used for the data collection, is the survey, which was carried out to the people who are part of the company M.J. Torres and that are in charge of the warehouse, which allowed to know the way in which the inventory is managed in this organization. In the company M. J Torres there are problems such as the poor record of the information in the inventories by the person in charge of the task, the accumulation of large volumes of inventory that are not located in places where they can be found quickly and the discrepancies between the physical inventory and the digitally registered. As a result of inefficient and inefficient inventory management, this has become an impediment for the company to optimize the profit generated by sales, it is an obstacle to carry out an adequate control of the costs that allows to elaborate a good administrative process of quality standardization within the organization. According to the investigation carried out, there is a poor inventory control, which can translate into losses for the company, since it can not efficiently meet the demand of its customers. In this way the control of the inventory is a very important element for the development of the company M.J. Towers; a bad administration, it is very important that companies have their inventory carefully controlled, monitored and orderly, given that it depends on the provision and distribution of what is properly, making it available at the time indicated.